Partial purification And Thermodynamic Analysis of Thermost able A-Amylase From Bacillus Cereus Mtcc 1305 - KR. SUGUMARAN,; V. PONNUSAMI,; S. N. SRIVASTAVA, (International Journal of Pharma and Bio Sciences, 2012)
This study investigated the ability of Bacillus cereus MTCC-1305 to produce alpha amylase and its kinetics, thermodynamic characterization using submerged fermentation. The enzyme was then purified by acetone precipitation and anionic‑exchange chromatographic technique. Effects of pH, substrate concentration, and temperature on enzymatic reaction were studied after partial purification of enzyme solution. Thermal stability was investigated at 90˚C. The half-life period of the enzyme was obtained as 7.42 min at 90˚C. Inhibition kinetic study was investigated using 0.05 M CuSO4 solution as an inhibitor. Maximum velocities of reaction were found to be 0.13g/l min (without inhibitor) and 0.061 g/l min (with inhibitor). Km and KI values were obtained to be 6.49 g/l and 0.3526 g/l respectively from Line-weaver Burke plot. Thermodynamic variables such as enthalpy change of activation ∆H*, entropy change of activation ∆S* were obtained from effect of temperature on enzyme activity study using transition state theory